Does open innovation foster productivity? Evidence from Open Source Software (OSS) firms - Elad Harison; Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2008)
The primary findings of our study suggest that software firms that adopt the OSS-based business model are notably less productive than companies that merely offer proprietary software solutions. Our estimation results further show that the OSS business model adopters have not become notably less productive after beginning to supply OSS. Therefore, its seems that not the use of the OSS business model as such has reduced the OSS firms' labour productivity but the firms that employed the OSS business model during the sampled years were, on average, of lower labour productivity type. Though the OSS business model use has not substantially improved the performance of software firms, we find that the OSS business model adopters strategically using the source code made available by the OSS community as part of their new software products, have performed better in terms of labour productivity than other adopters of the OSS business model.
Keywords: D24; J24; L17; L86; O33; 330; open source software; business strategies; open innovation; labor productivity; IT-Industrie; Softwareindustrie; Open Source; Produktivität; Finnland